How Smart Technology Affects the Well-Being and Supportive Learning Performance of Logistics Employees? - Jiang, Fei; Wang, Li; Li, Jian-Xin; Liu, Jie (Frontiers in Psychology, 2022)
The rapid improvement of technologies such as artificial intelligence in recent years has resulted in the development of smart technologies (ST) that can influence learning performance in different fields. The purpose of study is to explore the link between smart technology and learning performance. Using the S-O-R model as a framework, the researchers argue that smart technology (Stimuli) will increase corporate trust, self-efficacy, and well-being (Organism), resulting in improved learning performance (Response). The current model regards corporate trust and self-efficacy as relationship factors and investigates their direct influence on employee well-being and learning performance and the mediating role played by these variables. Additionally, the function of employee well-being in moderating the relationship between corporate trust, self-efficacy, and employee learning performance is also explored. The respondents (n = 516) in the present study are made up of employees from 10 logistics companies located in China. The data analysis is conducted using the AMOS software. The results show that that smart technologies can affect learning performance through corporate trust, self-efficacy, and employee well-being. The implementation of smart technology initiatives by corporations may provide positive workplace outcomes for employees (increased well-being), corporations (more engagement in workplace learning performance), and the relationship between employees and the companies that employ them (corporate trust and self-efficacy).